Physiological response to thermal stress in hair-sheep ewes during subtropical summer - Gómez-Guzmán, Javier Alejandro; Vázquez-Armijo, José Fernando; Hernández-Meléndez, Javier; Lara-Rivera, Ana Laura; Parra-Bracamonte, Gaspar Manuel (Revista Científica de la Facultad de Ciencias Veterinarias, 2021)
With the aim to assess the effect of short-term thermal stress on physiological traits of ewes an experiment was designed. Fourteen hair sheep ewes were selected during early reproductive management and randomly segregated in two groups. Control group (CG) with indoor conditions, and an experimental group (EG) under continuous outdoor conditions without shadow accessing during 14 days (d). Respiratory frequency (RF), rectal temperature (RT) and infrared image temperatures were estimated. Traits were measured for 8 d twice a d (9:00 am and 15:00 pm). Environmental temperature and humidity were monitored, and temperature and humidity index was estimated. All physiological and environmental traits showed significantly variation by group and time of measurement (P < 0.001). RT and RF were significantly higher for EG and during pm measurements. Environmental conditions indicated thermal stress conditions for outdoor EG during the afternoon was related ultimately with respiratory mechanism as the main indicator of continuous thermal stress. Head infrared image temperature was a good predictor of body temperature.